2006
DOI: 10.1097/01.tp.0000197555.16093.98
|View full text |Cite
|
Sign up to set email alerts
|

Elicited Antibodies in Baboons Exposed to Tissues from ??1,3-Galactosyltransferase Gene-Knockout Pigs

Abstract: Anti-nonGal Abs developed after GalT-KO pig heart Tx into baboons. The most potent of these antibodies appeared to detect antigens shared by the three pig haplotypes tested. It remains unclear whether these antibodies are directed towards shared SLA determinants or other pig antigens, and whether antibodies with specificity for allelic SLA determinants are also present, but at lower titer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 22 publications
1
28
0
Order By: Relevance
“…Transplantation of porcine hearts from α(1,3)-galactosyltransferase knockout pigs has increased graft survival over previous studies [42]. However, anti-non Gal antibodies (which induce delayed xenograft rejection) did develop in baboons receiving the transplanted porcine hearts within several weeks following transplantation [43]. Thus, the first steps have been made to successfully combat HAR, although hyperacute rejection and delayed rejection cannot be completely ablated using this approach.…”
Section: Advances In Xenotransplantation Of Porcine Tissuesmentioning
confidence: 94%
“…Transplantation of porcine hearts from α(1,3)-galactosyltransferase knockout pigs has increased graft survival over previous studies [42]. However, anti-non Gal antibodies (which induce delayed xenograft rejection) did develop in baboons receiving the transplanted porcine hearts within several weeks following transplantation [43]. Thus, the first steps have been made to successfully combat HAR, although hyperacute rejection and delayed rejection cannot be completely ablated using this approach.…”
Section: Advances In Xenotransplantation Of Porcine Tissuesmentioning
confidence: 94%
“…Co-stimulation blockade in the Kuwaki study appeared to be more effective at preventing the non-Gal humoral response than in the accompanying kidney xenograft study [6 ], because elicited circulating non-Gal antibodies were only detected after graftectomy and cessation of treatment [10]. Nevertheless the Gal KO hearts were still rejected, and it was suggested that activation of graft endothelium by low levels of non-Gal antibodies was at least partly responsible [10].…”
Section: Introductionmentioning
confidence: 98%
“…The cytotoxicity of AGAB is due in part to the high abundance of the preformed antibody, its strong induction posttransplant, and the abundance of the Gal antigen on a diverse set of glycolipids and glycoproteins. In contrast, non-Gal antibody and antigens seem to be much less abundant (23) and may be predominantly EC proteins (24), although additional carbohydrate antigens may yet be defined (25). These differences suggested that the elimination of the Gal antigen (group 3) might significantly alter the histopathology or tempo of xenograft rejection.…”
Section: Discussionmentioning
confidence: 87%